Prevalence and risk factors of coronary artery disease in patients with chronic viral hepatitis. Issue 8 (6th November 2015) - Wang, Chunya; Zhao, Pan; Luo, Ping; Liu, Weiwei; Wang, Hao; Zhao, Quanming
Abstract: Objectives: Patients with chronic viral hepatitis usually present metabolic abnormalities and hemodynamic changes, which are known factors associated with the development of coronary artery disease (CAD). This study aims to determine the risk factors of incident CAD in these patients. Methods: We identified 193 patients who subsequently developed CAD amongst 37, 840 cases diagnosed as chronic viral hepatitis from January 2007 through December 2013. Results: In these patients, 141 had hepatitis B virus infections and 52 had hepatitis C virus infections. There was a male preponderance (65.9%). The median age at the diagnosis of hepatitis was 51 years. In the univariate analysis, patients aged ≥ 51 years had shorter median periods from the diagnosis of hepatitis to the onset of CAD than patients aged < 51 years (50 versus 96 months, p < 0.001), and patients with hypertension had shorter median durations compared to those without hypertension (48 versus 96 months, p < 0.001). Statistical significance also existed between patients with different etiologies ( p = 0.004). In the multivariate analysis by Cox regression, age at the diagnosis of hepatitis ( p < 0.001; hazard ratio (HR), 1.041; 95% CI, 1.027–1.056) and hypertension (with versus without, p < 0.001; HR, 1.925; 95% CI, 1.419–2.611) were revealed. Conclusions: Age at diagnosis of hepatitis and hypertension appeared to be independent risk factors of incident CAD in these patients. This topic deserves further studies.